High capacity, low resilience: The 'developmental' state and military–bureaucratic authoritarianism in South Korea. Issue 1 (January 2018) - Hellmann, Olli
This article argues that high levels of state capacity are not a sufficient condition for consolidating autocratic rule. Rather, whether non-democratic rulers can harness the infrastructural power of the state to implement strategies of regime stabilization depends on three crucial factors: the state's social embedding; the international context; and the extent of elite cohesion. The paper develops this argument through a case study of the military–bureaucratic regime in South Korea (1961–1987), which – despite a high-capacity 'developmental' state at its disposal – failed to maintain high levels of resilience.